(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Champions in the field of sports are born and then groomed in later life. The aim of this studywas to find out the effect of swiss ball training, core board training and resistance tube training to improvethe leg strength among the college football players. Randomly selected 60 intercollegiate level footballplayers were randomly divided into four group consisting of 15 players in each group. Group I wasassigned to undergo swiss ball training, Group II to undergo core training, Group III to undergoresistance training for 8 weeks and the fourth group was control group, which did not underwent anytraining Prior to experimental treatment, all the subjects were measured of their leg strength throughstanding broad jump, which formed pre test scores. The experimental group I underwent swiss balltraining consists of Transverse Abdominous Exercise on Swiss Ball, Reverse Bride on Swiss Ball, BackExtension on the Ball, Abdominal Curl Rotation, Abdominal Curl on Ball, Superman Exercise on SwissBall, Back Extension on the Ball, Side Plank with Knee Rotation, The experimental group II underwentcore board training consists of Plank with hands on Core Board, Reverse Plank with hands on CoreBoard, Rocking in Quadruped, Push ups on Core Board, Kneeling Hings, The experimental group IIIunderwent resistance tube training consisting of Partner Tubbing Assisted Acceleration Drill, TowedRunning (Pullying), Partner Resisted start. The experimental period was for 8 weeks and immediatelycompleting the experimental period, the subjects were measured of their leg strength, which formed posttest scores. Control group was not given any specific treatment. The initial and final means werecompared to test significance through Analysis of Covariance (ANCOVA) RESULTS The obtained Fvalues on the scores of pre test means and post test means were less than the required table value. Theadjusted means were determined and analysis of covariance was done and the obtained F value 633.6was greater than the required F value and found that the swiss ball exercises, core board exercises andresistance tube training were significantly improved the leg strength of the football players. The pairedadjusted means proved from that resistance tube training was superior in improving leg strengthfollowed by core board exercises and then by swiss ball exercises compared to control group. Thecomparisons between the experimental groups proved that resistance training was significantly betterthan core board training and swiss ball training in improving leg strength of the intercollegiate levelfootball players.It was concluded that even through all the three experimental treatments were improvedleg strength of football players, resistance training was found to be superior which can be included inthe training schedule for football players.